EFEKTIVITAS PELAKSANAAN PUBLIC RELATION DALAM PEMBUATAN SIM DI SATUAN LALU LINTAS POLRES DI KABUPATEN BONE - Jumriati, A; Parawangi, Anwar; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTHis study purposed to find out the effectiveness of the implementation of public relations in making driver's license at the Traffic Police Unit in Bone Regency, using qualitative research methods, the number of informants in the study were 8 people. The results of the study showed that 1) the achievement of public relations goals consisted of providing socialization of the importance of driver's license to the community, visited to elementary schools as a preventive measure or rare, providing information when making driver's license directly, but the purpose of public relations had not been implemented evenly because some people did not know the form of public relations carried out. 2) The timing of public relations carried out by the Traffic Unit of the Bone Regency Police was on time, understanding their duties and responsibilities. However, some people felt that the implementation of public relations was not in accordance with the reality because it took a long time to make driver's license. 3) The benefits of public relations had not been fully achieved because traffic awareness was still lacking and the level or number of ticketing was still high and some people had not felt the benefits of public relations and making driver's license was not in accordance with management because it exceeded one day.Keywords: Effectiveness, Public Relations and SIM